2019
DOI: 10.1080/15384101.2019.1648956
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: The involvement of FBP1 in prostate cancer cell epithelial mesenchymal transition, invasion and metastasis by regulating the MAPK signaling pathway

Abstract: Prostate cancer (PCa) is a frequently occurring malignancy in males, and epithelial mesenchymal transition (EMT) plays a critical role in PCa metastasis. Thus, developing biomarkers inhibiting EMT may provide significance for treatment of PCa. Hence, the aim of the current study was to investigate the mechanism by which FBP1 gene silencing influences PCa cell EMT, invasion and metastasis by mediating the MAPK pathway. PCa cell lines exhibiting the highest FBP1 expression were selected and treated with plasmids… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 33 publications
2
12
0
Order By: Relevance
“…Fructose‐1,6‐bisphosphatase (Fbp1) is a rate‐limiting enzyme of gluconeogenesis that catalyses the splitting of fructose‐1,6‐bisphosphate into fructose 6‐phosphate and inorganic phosphate 8 . Fbp1 reportedly plays a critical role in several diseases, including type 2 diabetes mellitus, 9 cancers 10‐12 and acute liver failure 13 . Kaur et al 9 reported that Fbp1 can be considered a potential target for the treatment of type 2 diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…Fructose‐1,6‐bisphosphatase (Fbp1) is a rate‐limiting enzyme of gluconeogenesis that catalyses the splitting of fructose‐1,6‐bisphosphate into fructose 6‐phosphate and inorganic phosphate 8 . Fbp1 reportedly plays a critical role in several diseases, including type 2 diabetes mellitus, 9 cancers 10‐12 and acute liver failure 13 . Kaur et al 9 reported that Fbp1 can be considered a potential target for the treatment of type 2 diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…FBP1 overexpression inhibits the proliferation, migration, invasion and tumorigenesis of cholangiocarcinoma cells by inhibiting the Wnt/β pathway [ 33 ]. FBP1 gene silencing could activate the MAPK pathway and then promote cell EMT, invasion and metastasis in prostate cancer [ 34 ]. Several studies have found that PLOD2 induces epithelial-mesenchymal transition (EMT) mainly through the PI3K / AKT signaling pathway [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Consistently with DUSP1 effects on MAPK activity, the ERK pathway is one of the major oncogenic signals in human cancers because its activation leads to an increase in proliferation, invasion, and metastasis [ 32 ]. Particularly in prostate cancer, the ERK pathway is often hyperactivated [ 33 ], acts as an inducer of cell migration and invasion [ 34 , 35 ] through a Snail-mediated mechanism [ 36 ], and is involved in the effects of different molecules on these processes [ 37 , 38 , 39 ]. In addition, the JNK pathway has also been described to be important as a pro-tumorigenic signal through Snail regulation in different tumors [ 40 , 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%